Sensitivity analysis of the fracturing fluid rheology effect on the hydraulic fracture geometry in the terrigenous reservoirs - V. V. Savelev; I. N. Ognev (Georesursy, 2024)
Hydraulic fracturing is a technologically complex procedure that is influenced by many factors. Some of them cannot be changed, such as the geomechanical parameters of the target formation or the orientation of the stresses in the formation. But other parameters can be adjusted: proppant type, fluid type or injection mode. In this paper, modelling of the effect of fracture fluid rheological parameters on fracture geometry has been carried out. Two software products, RN-GRID from Rosneft and FracPRO from GTI Energy, were used to create the models, and analytical calculations were performed. Identical models were created in which rheological parameters were changed and changes in fracture geometry were analysed. The presented theoretical data and dependencies can help specialists to form an idea of the processes that take place during the hydraulic fracturing, and more consciously approach the calculations.